2017
DOI: 10.1186/s12913-017-2359-0
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural validation of health literacy measurement tools in Italian oncology patients

Abstract: BackgroundThe aim of this study was to assess the psychometric characteristics of four Health Literacy (HL) measurement tools, viz. Newest Vital Sign (NVS), Short Test of Functional Health Literacy in Adults (STOFHLA), Single Item Literacy Screener (SILS) and Single question on Self-rated Reading Ability (SrRA) among Italian oncology patients.MethodsThe original version of the tools were translated from the English language into Italian using a standard forward-backward procedure and according to international… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 15 publications
5
10
0
Order By: Relevance
“…In our study, 34.6% of respondents demonstrated inadequate and marginal health literacy, a figure similar to other studies where the prevalence of inadequate health literacy varied between 32% and 59% [8,12,13,14,19,20]. Additionally, the healthcare of the respondents was not significantly influenced by gender [13,21]; however, other studies [12,22,23,24] that referenced gender found it was a relevant factor in determining health literacy. The overall health literacy score of study respondents decreased as their age increased, a similar pattern to many other studies [11,12,13,14,15,16,17,18,19,20,21,22,24,25,26,27,28,29,30], while research groups in Japan and Switzerland did not categorize age as a relevant factor in individual health literacy in their study populations [31,32].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In our study, 34.6% of respondents demonstrated inadequate and marginal health literacy, a figure similar to other studies where the prevalence of inadequate health literacy varied between 32% and 59% [8,12,13,14,19,20]. Additionally, the healthcare of the respondents was not significantly influenced by gender [13,21]; however, other studies [12,22,23,24] that referenced gender found it was a relevant factor in determining health literacy. The overall health literacy score of study respondents decreased as their age increased, a similar pattern to many other studies [11,12,13,14,15,16,17,18,19,20,21,22,24,25,26,27,28,29,30], while research groups in Japan and Switzerland did not categorize age as a relevant factor in individual health literacy in their study populations [31,32].…”
Section: Discussionsupporting
confidence: 89%
“…In this study, health literacy among respondents living in urban communities was significantly higher in comparison to those who lived in rural communities, as was found by Parker [34]. Education level also had a significant impact on health literacy in several other studies [12,13,14,17,21,29,30,35], but not one in Japan [31].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The other tools were used in a limited number of studies, from one to three each (Table 1). Most studies investigated HL using selfreported comprehension items 26,27,30,33,34,36,38,44,[48][49][50]54,55,58,60,61,67,68,[70][71][72][74][75][76]78,81,83,85,86 Patients with chronic diseases were investigated in 25 studies 28,35,37,38,41,42,46,49,66,68,69,71,74,77,79,82,85 , whereas a smaller number of studies (n = 6) looked at oncology patients 47,61,75,…”
Section: Characteristics Of the Studies Included In The Proportion Meta-analysismentioning
confidence: 99%
“…In Ireland 10,30,37,38,41,42,49 , the pooled estimates varied between 19% (95% CI: 17-22%, df = 4, Q = 7.6, I 2 = 46.8%), 40% (95% CI: 37-43%), 41% (95% CI: 21-65%; df = 3, Q = 194.9, I 2 = 98.4%), and 65% (95% CI: 46-81%). Italy low HL pooled estimates were by self-reported comprehension items 61,65,66 42% (95% CI: 33-51%; df = 2, Q = 12.4, I 2 = 84.5%); by reading or numeracy comprehension items 61,66,67 , 38% (95% CI: 35-41%; df = 2, Q = 1.5, I 2 = 0.0%); by word recognition items 64,65 , 72% (95% CI: 32-93%; df = 2, Q = 70.8, I 2 = 97.9%); and by mixed method 58 , 54% (95% CI: 51-57%). As for Portugal 54,55,57,59,70 , the low HL prevalence estimates varied between 21% (95% CI: 8-46%, df = 5, Q = 86.1, I 2 = 96.5%), 29% (95% CI: 6-73%, df = 4, Q = 139.1, I 2 = 98.2%), and 50% (95% CI: 48-52%).…”
Section: Proportion Meta-analysis Of Low Health Literacy By Countrymentioning
confidence: 99%